2011
DOI: 10.1016/j.jpsychores.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Types of fatigue in sarcoidosis patients

Abstract: Types of fatigue in sarcoidosis patientsde Kleijn, W.P.E.; Drent, M.; Vermunt, Jeroen; Shigemitsu, H.; de Vries, Jolanda General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
2
27
0
1
Order By: Relevance
“…Fatigue was the most frequent symptom reported by patients with sarcoidosis of different degrees of activity [3]. Research carried out in Germany on 1,197 patients showed that nearly 62% of men and 74% of women complained of fatigue [18]. Korenromp et al in the Netherlands examined 75 patients with sarcoidosis, and 76% of them reported fatigue in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue was the most frequent symptom reported by patients with sarcoidosis of different degrees of activity [3]. Research carried out in Germany on 1,197 patients showed that nearly 62% of men and 74% of women complained of fatigue [18]. Korenromp et al in the Netherlands examined 75 patients with sarcoidosis, and 76% of them reported fatigue in the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the research by Miller [18,24], 67% of patients stopped during the test due to "weakness of the lower extremities", www.pneumonologia.viamedica.pl…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that depressive symptoms are negatively associated with and affect patients' fatigue scores [11,14,15]. In addition, the relationship between fatigue and depressive symptoms parallels the findings of other chronic illness, such as diabetes, chronic obstructive lung disease, cardiac disease and rheumatoid arthritis [41].…”
Section: Fatigue and Depressive Symptomsmentioning
confidence: 94%
“…Small fibre neuropathy SFN, a frequently bothersome symptom in a substantial number of sarcoidosis patients, can be linked to fatigue [11,56]. Although SFN may be difficult to diagnose, its identification can lead to possible targeted treatments, including TNF inhibitors [7,63] or intravenous immunoglobulin [64].…”
Section: Sleep Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation